Moringa Oleifera Treatment Prevents Crude Oil Tainted Diet Imposed Toxicity in Rats - Achuba F.I.* , Ubogu L.A. , Ekute B.O. (Sokoto Journal of Medical Laboratory Science)
Previous researches have documented the health and nutritional benefits of Moringa tree. The aim of this study was to evaluate the health benefits of Moringa oleifera leaves toward protecting against hydrocarbon- adulterated diet-related effects on Wistar albino rats. Rats were mobilized and fed hydrocarbon adulterated diet that was pre-treated with ground Moringa leaves. Liver, kidney and cardiovascular disease indices were determined and values evaluated relative to rats fed diet without hydrocarbon. Significant (p<0.05) hepatic derangement occasioned by changes in liver function enzymes and protein profile were observed. Similarly, kidney impairment markers were observed to be significantly altered by hydrocarbon tainted feed and significant (p<0.05) change in lipid levels that predisposes subjects to atherosclerosis. Generally, Moringa oleifera leaf powder in diet positively modulated the values of both liver, kidney and atherosclerotic markers close to values in control rats. This study establishes the protective effect of Moringa oleifera complemented diet against hydrocarbon- induced harmfulness